1984
DOI: 10.1172/jci111588
|View full text |Cite
|
Sign up to set email alerts
|

Response to immunization with Haemophilus influenzae type b polysaccharide-pertussis vaccine and risk of Haemophilus meningitis in children with the Km(1) immunoglobulin allotype.

Abstract: A bstract. In experimental animals, immune responses to certain antigens are regulated by immunoglobulin allotype-linked genes. In an effort to detect such genes in humans, we examined the antibody responses of 74 healthy children with different Km(l) or Gm(23) allotypes to a Haemophilus influenzae type b vaccine (type b polysaccharide capsule-pertussis vaccine). The anticapsular antibody responses of black or white children with the Km(1) allotype were 4.6-to 9.5-fold higher than those of children who lacked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In one case, conjugation of polyribosylribitol phosphate with a carrier protein (outer-membrane protein conjugate) reversed the association of the Km(1)-negative allotype with low antibody responsiveness to H. influenzae type b vaccine in African American children [61]. In another case, the Km(1)-positive allotype was associated with a decreased risk of Haemophilus meningitis in African Americans but not in whites [62]. Interestingly, the Km(1)-positive allotype has been associated with higher total IgG2 levels in African Americans, compared with those in whites [37]; this finding might, in part, explain the altered immune response of African Americans to certain polysaccharide vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, conjugation of polyribosylribitol phosphate with a carrier protein (outer-membrane protein conjugate) reversed the association of the Km(1)-negative allotype with low antibody responsiveness to H. influenzae type b vaccine in African American children [61]. In another case, the Km(1)-positive allotype was associated with a decreased risk of Haemophilus meningitis in African Americans but not in whites [62]. Interestingly, the Km(1)-positive allotype has been associated with higher total IgG2 levels in African Americans, compared with those in whites [37]; this finding might, in part, explain the altered immune response of African Americans to certain polysaccharide vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studics indicate that genetic factors, particularly genes associated with certain Gm and/or Km immunoglobulin allotypes, may be associated with altered responsiveness to vaccines containing bacterial polysaccharides (17)(18)(19). In addition, black children lacking the Km(1) allotype have an increased relative risk of developing meningitis caused by Hib (1 7).…”
mentioning
confidence: 99%
“…Such racial disparities in genetic associations, however, are not unprecedented. For instance, in a study involving AA and CA children with Haemophilus meningitis, the KM1 allotype was found to be associated with a lower relative risk of the disease in AA children, but the risk of meningitis was not decreased in the CA children with the KM1 allotype [17]. The association of KM3 with SVR in AA subjects observed here might be a result of its epistatic interaction with another genetic marker whose frequency is different in AA and CA populations.…”
Section: Resultsmentioning
confidence: 56%